2022
DOI: 10.3389/fphys.2021.787521
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deletion of the Mechanistic Target of Rapamycin From the Renal Collecting Duct Principal Cell in Mice Down-Regulates the Epithelial Sodium Channel

Abstract: The mechanistic target of rapamycin (mTOR), a serine-threonine-specific kinase, is a cellular energy sensor, integrating growth factor and nutrient signaling. In the collecting duct (CD) of the kidney, the epithelial sodium channel (ENaC) essential in the determination of final urine Na+ losses, has been demonstrated to be upregulated by mTOR, using cell culture and mTOR inhibition in ex vivo preparations. We tested whether CD-principal cell (PC) targeted deletion of mTOR using Cre-lox recombination would affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In agreement with these studies, Chen et al showed that deletion of mTOR from the PCs in mTOR fl/fl *Aqp2Cre mice CD resulted in reduction of all three ENaC subunits at the protein level and attenuated the ability to maintain Na + homeostasis in response to low NaCl diet and benzamil injection. 94 Although deletion of mTOR would influence both mTORC1 and mTORC2 activity, and the current study did not investigate which protein complex mainly played a role in their mice model, SGK1 phosphorylation was decreased in the cortex of KO mice along with increased ubiquitination of α-ENaC, in line with the current mTORC2-SGK1 signaling pathway consensus. 94 Aside from SGK1, SGK3 also modulates Na + transport in the CD through ENaC activity indirectly in a similar manner as SGK1.…”
Section: Ductmentioning
confidence: 59%
See 1 more Smart Citation
“…In agreement with these studies, Chen et al showed that deletion of mTOR from the PCs in mTOR fl/fl *Aqp2Cre mice CD resulted in reduction of all three ENaC subunits at the protein level and attenuated the ability to maintain Na + homeostasis in response to low NaCl diet and benzamil injection. 94 Although deletion of mTOR would influence both mTORC1 and mTORC2 activity, and the current study did not investigate which protein complex mainly played a role in their mice model, SGK1 phosphorylation was decreased in the cortex of KO mice along with increased ubiquitination of α-ENaC, in line with the current mTORC2-SGK1 signaling pathway consensus. 94 Aside from SGK1, SGK3 also modulates Na + transport in the CD through ENaC activity indirectly in a similar manner as SGK1.…”
Section: Ductmentioning
confidence: 59%
“…94 Although deletion of mTOR would influence both mTORC1 and mTORC2 activity, and the current study did not investigate which protein complex mainly played a role in their mice model, SGK1 phosphorylation was decreased in the cortex of KO mice along with increased ubiquitination of α-ENaC, in line with the current mTORC2-SGK1 signaling pathway consensus. 94 Aside from SGK1, SGK3 also modulates Na + transport in the CD through ENaC activity indirectly in a similar manner as SGK1. 95 It is currently not known if mTOR signaling is responsible for SGK3-mediated activation of these transporters.…”
Section: Ductmentioning
confidence: 59%
“…Another recent study in which AQP2-Cre was used to KO connecting tubule/collecting duct mTOR also showed defects in SGK1 and ENaC. 22 These reports support an important role of mTORC2 in regulating renal tubular K + secretion, however, key aspects remain unknown or controversial: (1) Is mTORC2 a permissive factor, or an acute mediator of aldosterone-independent regulation of K + secretion in vivo? (2) Are ENaC and ROMK both targets of acute and/or longer term effects of K + ?…”
Section: Introductionmentioning
confidence: 92%
“…Hyperkalemia became lethal when animals were treated with the ENaC inhibitor triamterene suggesting a more profound defect in ROMK than in ENaC [ 60 ]. It is notable that in contrast with Rictor KO mice [ 60 ], either acute treatment of mice with an mTOR inhibitor [ 56 ] or mTOR gene deletion [ 27 ] markedly reduces ENaC activity. Although these apparently conflicting findings require additional study to reconcile, they are consistent with the possibility that in vivo mTORC1 and mTORC2 are both able to stimulate ENaC (via SGK1), while only mTORC2 regulates ROMK.…”
Section: The Aldosterone-mr-sgk1 Signaling Module Regulates Enacmentioning
confidence: 99%